(untitled) (Revista de Crítica Literaria Latinoamericana, 2012)
This article charts the development of Westphalen’s poetry, focusing on his two earliest works. I highlight the surrealist and vanguard influences on his work, and illustrate the social and political climate that enveloped Peru and shaped the creation of Westphalen’s poetry. Rooted in the idea of freedom of the artist, Westphalen uses silence and the absence of “I” to imbue his poetry with an air of mystery. He also uses landscapes to create “another world”. Furthermore, Westphalen’s use of vocabulary and diction informs his poetry and the dynamism of the artist that he believed in.